Asymmetric Synthesis of Diastereo‐ and Enantiopure Bioxahelicene 2, 2′‐Bipyridines. Issue 37 (30th August 2018) - Klívar, Jiří; Šámal, Michal; Jančařík, Andrej; Vacek, Jaroslav; Bednárová, Lucie; Buděšínský, Miloš; Fiedler, Pavel; Starý, Ivo; Stará, Irena G.
Abstract : A versatile asymmetric synthesis of five C 2 symmetric enantio‐ and diastereopure bioxa[5]‐ and bioxa[6]helicene 2, 2′‐bipyridines was developed. It relied either on a double intramolecular [2+2+2] cycloisomerization of dicyanotetrayne (forming simultaneously the 2, 2′‐bipyridine unit and biazaoxahelicene backbone) or one‐pot/sequential intramolecular [2+2+2] cycloisomerization of triyne accompanied by an intermolecular haloazaoxahelicene reductive homocoupling. We reached an effective central‐to‐helical‐to‐axial chirality transfer that was controlled by the 1, 3‐allylic‐type strain and sterically constricted atropoisomerization of the embedded 2, 2′‐bipyridine unit. The chiroptical properties of the bioxahelicene 2, 2′‐bipyridines were studied along with their fluorescence properties. Abstract : Enantio‐ and diastereopure bioxahelicene 2, 2′‐bipyridines were synthesized employing dicyanotetrayne cycloisomerization or triyne cycloisomerization–haloazaoxahelicene homocoupling. An effective central‐to‐helical‐to‐axial chirality transfer was reached.